SNP Markers and its Impact on Crop Improvement - Das, Debasmita; Mishra, Rukmini (Asian Journal of Biological and Life Sciences)
With the advent of new technologies, methods and trends, the global progression in agricultural world is quite fast paced. However, it seems that Indian agriculture is yet to catch up to the new age technologies considering the practice of cultivation using the conventional methods can be still seen extensive. SNPs marker aided selection can prove to be an advantage for Indian agronomy. The cost effectiveness, fast and accurate mining for suitable allele specific marker and rapid detection makes this sequence-based marker the best option for a vast and versatile land like India, where its diverse topographic, geographic and climatic zones require equally distinct characteristics in crop genome to endure the environmental stress. The present review article summarizes the development of SNP markers and its applications in crop improvement.
Keywords: Crop Improvement; Marker Assisted Selection (MAS); Molecular Breeding; Molecular Marker; Sequence Based Marker; SNPs markers.